Basic Concepts of Islamic Economics Methodology - Nahlah Nahlah; Murtiadi Awaluddin; Amiruddin K; Ridwan Markarma (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2023)
The interest of scientists studying Islamic economic methodology lately is due to several factors, including some who think that the economy is not running well, still exists unemployment is growing along with high inflation rates, and there is almost no reliable solution to fix the local economic depression problems, regional financial crises, even global. This study aims to determine the basic concept of Islamic economic methodology according to several Islamic economists. The research method uses a literary approach from various journals, especially in the field of Islamic economic methodology, to be examined more deeply to obtain information about the basic concepts of Islamic methodology and what kind of methodology in Islamic economics is used by some Islamic economists. From the research results, the methodology in Islamic economics means building a theory (knowledge) and scientifically evaluating the theory (knowledge) by investigating the criteria, rationalizations, arguments, and justifications used. Meanwhile, Islamic economists' methodological approaches differ, but they have similarities in terms of the internalization of Islamic law in economic theory and practice. And in general, have an agreement to reject the conventional economic system that is contrary to Islam.